DISTANCE EDUCATION DISTANCE EDUCATION, DIGITAL TECHNOLOGY AND LEARNING OPPORTUNITIES FOR WOMEN IN SMALL ISLANDS IN NORTH MALUKU PROVINCE - Simabur, Lisda Ariani; Rahmat, Mamat; Elfrianto, Kevin; Cangara, Hafied (Jurnal Ranah Komunikasi, 2024)
Digital technology in providing learning opportunities for women on small islands in North Maluku in accessing higher education. Through distance education, in the case of the Open University has provided positive value to those who do not have the opportunity to enter higher education as conventional higher education. The purpose of this study is to find out the participation of women in small islands in North Maluku Province to participate in distance education facilitated by digital technology, as well as the strategies implemented by the Open University in explaining the learning platform to students. This study uses a descriptive qualitative method. Approach to literature review, interviews, and observations of distance education study objects and students in study groups on Sanana Island and Taliabu Island. The results of this study show that distance education implemented by the Open University through digital technology has facilitated better access to education for women who previously had learning limitations both in terms of tradition and geographically and economically on the islands of Sanana and Taliabu. The implication of this study is that the importance of distance education can be an effective means for women to achieve educational equality in small island areas.